Zonas de promiscuidade: trottoir do desejo sexual - Bortolanza, Elaine (2012)
The subject of this study is a moral web (where desire pulses for new arrangements and combinations) that consists of different elements mixed without order or criterion in a promiscuous way. In order to undo the sexuality device s knots, this study demonstrates that sexual desire is a dimension that cannot be reduced to the logic of representation. Rather it is beyond the identity politics and normative macropolitical games of the right. Desire battles insistently between: the individual and the collective; sex and the norm; bliss and love; and also I and the other . These battles form promiscuous zones. Therefore this study demonstrates two characters: the whores/prostitutes and the lovers. An empty and inconvenient sensation is experienced as we are in a zone of non-knowledge and non-recognition. This zone allows the expression of creative potential, mobilized exactly by the emptiness that occurs in the capitalist cultural regime. In the limits of the desire-sex-pleasure game zone, the concepts operate on the dynamics of affections, encounters and concrete experience. It is a game of sensations that desires sensitivity to tensions and paradoxes so that alternative ways for sexualities to vibrate can be reinvented. A fabulation concerning the metamorphosis of sexuality s minorities